Surgical Management and Histopathological Evaluation of a Mammary Tu mor in a Buffalo (Bubalus bubalis) (Indian Journal of Animal Production and Management, 2026)
The study aimed to define the histopathological features of mammary gland  tumours in buffaloes (Bubalus bubalis) in the form of a case series and to  highlight the importance of a microscopic study in the correct diagnosis and  treatment of mammary masses in large ruminants. Ten adult buffalo females introduced with hard, slowly growing masses of  the mamary glands of some three months. Each of the cases was surgically  handled, histologically processed representative tissues were examined under  the microscope. Clinical follow-up during the period of the postoperative  showed no lesion recurrence in all treated animals. Microscopic analysis showed a significant impairment of the normal structure  of the mammary glands. The mammary ducts were distended, irregular  and cystic at times. The ductal epithelium was hyperplastic, pleomorphic,  enlarged, and lost polarity with occasional loss of polarity. Fibrovascular  proliferation, congested blood vessels and multifocal inflammatory cells  infiltrations in the interductal stroma were seen. There were eosinophilic  secretory material and exfoliated epithelial cells in the lumina of the ducts.  Mitotic figures were not frequent. According to these histological characteristics, the lesion was categorised as  a low grade mammary ductal origin adenocarcinoma. Conclusively, mammary tumours are not common among buffaloes;  however, they must be included in the list of diagnostic possibilities of  chronic mammary masses. The histopathological investigation is crucial  in the accurate diagnosis, classification and proper clinical treatment of  tumours. Reporting of these cases will be a good source of information to  enhance knowledge, early diagnosis and management plan of the mammary  lesions in large ruminants.
Keywords: Buffalo, Mammary gland, Adenocarcinoma, Histopathology, Udder.